2001
DOI: 10.1159/000047094
|View full text |Cite
|
Sign up to set email alerts
|

Early Markers of Brain Damage in Premature Low-Birth-Weight Neonates Who Suffered from Perinatal Asphyxia and/or Infection

Abstract: We studied 57 low-birth-weight premature neonates, of whom 29 suffered from perinatal asphyxia and/or infection, while the remaining 28 did not and served as controls. We measured peripheral nucleated red blood cell (NRBC) absolute numbers as well as interleukin (IL)-1β, IL-6 and tumour necrosis factor (TNF)-α cytokine serum levels at 24 h postnatally and on days 3 and 7 following birth. Fourteen of the asphyxiated/infected neonates and 12 controls had neurologic assessments at the corrected postnatal age of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…A significant increase of IL-6 in the serum samples of PNH group compared with control group, observed in our study, is in agreement with this observation. Similar results have been found in other studies [29][30][31]. Moreover, some studies showed significantly higher values of IL-6 in CSF samples of children with asphyxia, but the serum samples were not tested in those studies [9,11,12,29].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A significant increase of IL-6 in the serum samples of PNH group compared with control group, observed in our study, is in agreement with this observation. Similar results have been found in other studies [29][30][31]. Moreover, some studies showed significantly higher values of IL-6 in CSF samples of children with asphyxia, but the serum samples were not tested in those studies [9,11,12,29].…”
Section: Discussionsupporting
confidence: 87%
“…While some studies found significantly higher levels of TNF-α in CSF samples, other studies demonstrated higher TNF-α levels in serum samples of hypoxic newborns [11,12]. In addition, some studies did not find increased levels of TNF-α after hypoxic injury [31,38]. In their study, Aly et al confirmed increased levels of TNF-α in both, serum and CSF samples [12].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Nearly 50% of term-born infants suffering severe HIE die within weeks of birth, while up to 25% of those surviving exhibit permanent neuropsychological dysfunction [7]. Similarly, a 50% mortality rate exists for preterm infants experiencing severe HI, with 80% of survivors experiencing long-term complications [19], including reductions in cerebellar [20], cortical, and hippocampal volumes [21] associated in turn with cognitive and behavioral deficits, deficits in verbal and language domains [22, 23], reduced IQ measures [24], cerebral palsy, and mental retardation [25]. What is surprising, however, is the disproportionate incidence of, and increased severity of effects following, neonatal HI injury in males.…”
Section: Introductionmentioning
confidence: 99%
“…Due to medical advances, more infants with HI now survive than in the past, leading to an increase in the numbers of children with associated behavioral deficits later in life [2,27,28,29,30,31]. Indeed, despite the varying etiologies noted above, both term and preterm HI populations show increased frequencies of language deficits [32,33,34,35,36,37], memory impairments [38,39,40,41] and developmental disorders such as ADHD [31,42,43,44,45,46,47].…”
Section: Introductionmentioning
confidence: 99%